Análisis del desempeño laboral en el Gobierno Autónomo Descentralizado Municipal del cantón Sucre período 2020 - Valdiviezo Vera, Osmara Viviana (2021)
Public institutions strive every day to provide quality public services to all citizens, however, they have problems to successfully meet their institutional objectives. Currently the municipalities are trying to reduce these negative aspects that affect their actions. Under this orientation, the objective of the research is to analyze the influence of work performance for the improvement of Human Talent of the Autonomous Decentralized Municipal Government of the Sucre canton period 2020. The scientific methods that were used are; inductive and deductive, which gave theoretical support to the work, on the other hand, the field research allowed the extraction of information through interviews and observation, which helped to know the current state of public servants in their work performance. Similarly, the surveys were applied to 111 professionals whose significant results showed with 77% that the workplace is appropriate to carry out their daily tasks in an ideal way, 88% also indicated that they receive little professional training, while 44 % pointed out the scarce communication between staff and immediate boss, which has generated less effective communication. Finally, it was concluded that it is important for the institution to embrace the improvement plan set out to mitigate these problems that directly affect the institution's human talent, which was shared with the corresponding authorities.